Cognitive and social cognition deficits in Huntington's disease differ between the prodromal and the manifest stages of the condition: A scoping review of recent evidence. (14th October 2021) - Cavallo, Marco; Sergi, Antonietta; Pagani, Marco
Abstract : Objective: Huntington's disease (HD) is a dramatic neurodegenerative disorder encompassing severe motor symptoms coupled to significant cognitive and social cognition deficits. However, it is not clear whether and how patients' neuropsychological profile changes between the prodromal and the manifest stages of the condition. The aim of the present in‐depth review is to consider cognitive and social cognition impairment in HD patients by differentiating deficits arising before diagnosis from those evident from the manifest phase onwards. Methods: Electronic databases were searched between January 1 st, 2010 and December 31 st, 2020 by using multiple combinations of keywords related to the investigation of neuropsychological profile in HD for preliminary search, and by defining strict selection criteria for studies to be included. Results: Forty‐two studies were included. Evidence suggests that the neuropsychological profile in HD reflects a complex pathological spectrum of deficits. It includes impairment in the realms of executive functions, memory, attention, information processing, and social cognition. Interestingly, patients' profiles differ significantly between the manifest and the prodromal stages of their condition, not only in quantitative terms but also from a qualitative point of view. Conclusions: Researchers and clinicians should thus include in clinical routine timely and specific neuropsychological assessments in order to monitor patients' cognitive status as time goes by, with the ultimate goal to implement effective clinical management strategies. Practitioner points: The neuropsychological profile in HD encompasses a complex pathological spectrum of deficits. Patients' profiles differ significantly between the manifest and the prodromal stages of their condition. Clinicians should include in everyday practice a timely and specific neuropsychological assessment. Detecting patients' cognitive status during the early stages of the condition already can contribute significantly to implement effective clinical management strategies.